Metallic Nanopopcorns: A New Multimodal Approach for Theranostics - Shende, Pravin; Deshpande, Gauraja (Current Nanoscience, 2021)
Background: Nanopopcorns are a novel class of metallic nanoparticles that demonstrate structural similarity to the grains of popcorns with theranostic activities for diseases like cancer and bacterial infection using Surface Enhanced Raman Spectroscopy-based detection. Objective: The objective of the present article is to highlight the importance of popcorn-shaped nanoparticles for the treatment of various disease conditions like cancer, diabetes, ulcerative colitis, rheumatoid arthritis, etc. Methods: Nanopopcorns enter the target cells via conjugation with various proteins, aptamers, etc. to kill the diseased cell. Moreover, external magnetic radiations are provided to heat these metallic nanopopcorns for creating hotspots. All such activities can be tracked via SERS mechanism. Results: Nanopopcorns create alternative and minimally-invasive treatment strategies for inflammatory conditions and life-threatening diseases. Conclusion: In the near future, nanopopcorn-based drug delivery system can be an interesting field for research in medicinal nanotechnology.
Keywords: cell imaging